Electrochemical exploration on hexadecylamine capped copper sulfide nanocubes using single source precursor for enhanced supercapacitor devices - C., Sambathkumar; K.R., Nagavenkatesh; M. Krishna, Kumar; N., Nallamuthu; S., Sudhahar; P., Devendran (Journal of energy storage, 2022)
Copper sulfide (CuS) based material has been broadly used in recent years because of its semiconducting and non-toxic nature. CuS nanocubes (NCs) were synthesized at low temperature by the solvothermal method using copper diethyldithiocarbamate (Cu[DTC]2) as a single-source precursor and the presence of hexadecylamine (HDA) as shape directing agent. As-prepared CuS NCs properties like thermal, phase, vibrational group, morphology and elemental were explored by different analytic tools. Further, the electrochemical behaviours of CuS NCs modified working electrode were examined in 1 M KOH electrolyte solution. It exhibits remarkable specific capacitance (Csp) of 1472.3 Fg−1 at 1 Ag−1 with excellent capacitive retention up to 93.6 % after 5000 charge-discharge cycles at the current density of 10 Ag−1. Besides, the two electrode asymmetric supercapacitor (ASC) device was constructed and it exhibits the Csp of 54 Fg−1 at 3 Ag−1. Moreover, even after 5000 cycles at a 7 Ag−1 of current density, the ASC device was able to retain internal capacitance retention of 91.2 % due to its high energy density of 21.68 Wh kg−1 and power density of 1272.92 W kg−1. After 5000 cycle's electrochemical evaluation of CuS NCs modified electrode were analyzed. These outcomes of electrochemical performance suggested that fabricated CuS||AC device has a bright future in energy storage application. [Display omitted] •CuS nanocubes have been successfully synthesized by solvothermal method using single source precursor.•CuS electrode exhibits Faradic pseudocapacitive behaviour and achieved excellent specific capacitance of 1472.3 Fg-1 at 1 Ag-1•Retention; 93.6% and 98.3% coulombic efficiency after 5000 cycles.•Fabricated CuS||AC device exhibits high energy density of 21.5 Wh kg-1 and power density of 1274.8 W kg-1.•After electrochemical performance electrode was tested PXRD, FT-IR, SEM and EDS.